Deriving a New Crustal Model of Northern Adria: The Northern Adria Crust (NAC) Model - Magrin, Andrea; Rossi, Giuliana (Frontiers in Earth Science, 2020)
We presented a new 3D model of the geophysical properties of the crust (namely depth of the Moho and VP, VS, density, Young’s modulus, and shear modulus) of the northern tip of the Adria microplate that we called NAC (Northern Adria Crust). The horizontal dimensions of the physical properties variations are optimized at 5x5 km and the vertical dimension at 1 km. NAC has been built by critically choosing and integrating all available information about the depth of the main interfaces and the physical properties of the crust. We started from a VP dataset, and we converted it in VS and density by using empirical relations, tuned through the comparison with the available data from local tomographic inversion, and taking into account the lithologies of the area. Uncertainties and reliability of the model are quantified, taking into account the data quality and the interpolation procedure. NAC has two versions, different in the structure of the Moho interface: the first considers one continuous surface for the whole area, while the second implies three separate surfaces for the Adria microplate, Eurasia and the Pannonian fragment. The differences between the two models are minimal, but the available data better sustain the solution of the fragmented crust. For its characteristics of multiparametric information and resolution, NAC can be precious for any purpose and use where a detailed knowledge of the crustal structure of this area is required. Moreover, it is easy to improve NAC, including new information on the crustal structures, when they will be available.